Reusing of Organic Waste from Tubifex sp. Substrate in nature - D. Shafruddin; W. Efiyanti; . Widanarni (Jurnal Akuakultur Indonesia)
This study was conducted to determine whether organic waste from the substrate of Tubifex sp. can be used as inoculants to produce them through culture.   Substrate used was the mix of mud and chicken manure by ratio of 1:1, placed on the container 80×20×15 cm, water elevation 2 cm, and water debit 300 ml/min.  Inoculants number was ranged from 57 to 60 Tubifex sp. per container. The length of Tubifex sp. body was ranged from 0.9 to 3.5 cm and an individual mean weight of 2.78 mg.   Organic waste applied was 500 g, 1000 g, and 1500 g.  Rearing was performed for 50 days.  During experiment chicken manure of 0.075 g/m2 was added into culture every day.  The results of study showed that higher population of Tubifex sp. (174,227 tails/m2; 413.7 gram wet weight) was obtained by using 1000 g of organic waste.  Thus, organic waste derived from the substrate of Tubifex sp. from the nature can be reused to culture Tubifex sp. at the controlled container.